Mercosur and the Pacific Alliance, more differences than coincidences? (2014)
Mercosur is going through difficulties, to which other integration processes in Latin America are not alien. In recent years there have been changes in the insertion strategies of the countries of the region, which show some differences in how to relate to developed economies such as the United States and the European Union and more recently with Asia Pacific. In short, Mercosur and the Pacific Alliance represent the two models of international insertion in the region, which leads us to wonder if we are really facing two processes with such different characteristics.